Managing Oil Wealth : The Case of Azerbaijan - Hobdari, Niko.; Aturupane, Chonira; Gvenetadze, Koba.; Le Borgne, Eric. (Washington, D.C. : International Monetary Fund, 2004)
Oil and gas production in Azerbaijan were projected to increase sharply in 2005 and 2006, respectively, reaching peaks of 1.3 million barrels a day in 2009 and 20 billion cubic meters a year in 2010. Although expected revenues over the next 20 years will be substantial, they are projected to return to 2004 levels by 2024. Managing this temporary windfall in a way that allows for economic diversification and increased living standards is the subject of this book, which provides extensive guidance based largely on lessons drawn from the experiences--mostly negative--of other countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet